COMMUNICATIVE LEARNING IN THE CLASSROOM INTERACTION : A Descriptive Study on First Grade Students in SMP Negeri 5 Bandung - Rianti, - (2006)
This paper is entitled "Communicative Learning in the Classroom Interaction (A Descriptive Study on First Grade Students in SMP Negeri 5 Bandung)". The purposes of this research are to describe how communicative learning occurred in the classroom interaction and to identify types of interaction in the classroom. To meet the purposes of the research, this study raises the questions relating to the principal feature of the COLT (Commumcative Orientation of Language Teaching) scheme proposed by Nunan (1992). SMP N 5 Bandung was taken as the setting of this research. The interactions between two teachers and learners of class 7C and 7K on first grade in the academic year 2005/2006 were recorded as subject of analysis. To examine the learning process and interaction, this research used qualitative approach by means of descriptive method. In collecting the data, the researcher employed video recording. The data obtained through observation was in the form oftranscribed interactions. The results of this research evidenced that communicative learning occurred through role-playing, discussion, conversation, and presentation. It was also found that the types of interaction occurred in the classroom are Teacher- Class (T-C), Teacher-Group (T-G), Teacher-Students (T-S), Student-Student (SS), Student-Content (S-C), and StudenMnterfece (S-I) interactions. Each of this interaction is influential in the classroom. Regarding the findings of the research, the researcher concludes that these communicative analysis can be used as self-monitoring for language teacher to create communicative classroom. Therefore, this study is useful to introspect teacher's and learners' performance in the classroom.